MODERN ASPECTS OF THE USE OF BREATHING EXERCISES IN THE PRACTICE OF A PHYSICAL THERAPIST IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Physical Culture and Sport: Scientific Perspective, 2022)
Chronic obstructive pulmonary disease (COPD) is an extension of respiratory system pathologies that are manifested by irreversible changes in the distal airways. In connection with the deterioration of the global ecological situation, the statistical registration of the incidence of COPD increases annually. The mortality rate for this pathology remains high.Breathing exercises must be included in the patient rehabilitation program. The main ones were static breathing, dynamic breathing, static diaphragmatic breathing, arbitrarily controlled or localized breathing, special breathing exercises and breathing exercises with dosed resistance. Sound gymnastics was transmitted in a special way, depending on what sound was received in accordance with the given meaning and in a certain way. Respiratory gymnastics was also used.The purpose of the work was to determine the peculiarities of the use of breathing exercises in the physical rehabilitation of patients with chronic obstructive pulmonary disease.Results: Identification of modern aspects of the use of breathing exercises in the practice of a physiotherapist in patients with chronic obstructive pulmonary diseaseConclusions and prospects for further research. COPD is a widespread pathology of the respiratory system, which appears as irreversible changes in the distal parts of the respiratory tract, which leads to significant economic and social damage, as a result of which there is an objective need to develop and implement individual programs for physical rehabilitation of this category of patients. Breathing exercises are a mandatory part of all physical rehabilitation programs for patients with chronic obstructive pulmonary disease.
Keywords: chronic obstructive legend fixation; physical rehabilitation; breathing exercises